Absence of T-box transcription factor 21 limits neuromuscular junction recovery after nerve injury in T-bet-knockout mice - Jablonka-Shariff, Albina; Broberg, Curtis; Snyder-Warwick, Alison K. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTerminal Schwann cells (tSCs), at the neuromuscular junction (NMJ), play critical roles in the repair of motor axon terminals at muscle, and rebuild neuronal signaling following nerve injury. Knowledge of mediators impacting tSCs post-nerve injury and in disease may guide beneficial therapies to improve motor outcomes. We previously found T-box transcription factor 21 (TBX21/TBET), classically associated with T-helper1 cells and immune cell recruitment, is expressed in tSCs at the mouse NMJ. The purpose of this study was to examine effects of Tbx21 absence during NMJ regeneration following peripheral nerve injury.MethodsWildtype (WT) and Tbet-knockout (Tbet-KO) mice underwent sciatic nerve transection and immediate repair. Functional muscle recovery assessment was performed with muscle force testing on mice at 2-, 3-, 4-, and 6-week (wks) and 6 months after nerve injury repair. Morphometric analyses of NMJ reinnervation, tSC number, and tSC processes were evaluated. Full NMJ reinnervation was defined as ≥75% coverage of endplates by axons. A minimum of three mice were evaluated in each group, and 50–100 NMJs were evaluated per mouse.ResultsTbet-KO mice had significantly diminished muscle function compared to WT mice at every time point beyond 3 weeks. Tbet-KO mice showed just over half of the muscle force generated by WT mice at 4 weeks and 6 weeks post-injury and repair. By 6 months, Tbet-KO mice generated only 84.1% the muscle force of WT mice. Tbet-KO mice showed significantly decreased levels of fully reinnervated NMJs compared to WT mice at each time point tested. Tbet-KO mice also showed a lower number of tSCs with reduced cytoplasmic processes beyond NMJ area and lower number of immune cells during process of NMJ regeneration.DiscussionOur findings show that the Tbx21 transcription factor promotes NMJ reinnervation to regain muscle function following nerve injury.